Examining the effect of underlying individual preferences for present over future on lung cancer screening participation: a cross-sectional analysis of a Korean National Cancer Screening Survey - Kui Son Choi; Yeol Kim; Jaeho Lee; Mina Suh; Seri Hong (BMJ Open)
Objectives This study aimed to examine the effect of underlying individual preferences for the present over that for the future on lung cancer screening participation.Setting We analysed the data from the Korean National Cancer Screening Survey in 2018.Participants 4500 adults aged 20–74 years old participated in the study.Design In this cross-sectional survey, multivariate logistic regression analysis was carried out to examine the association between subjects’ intention to participate in lung cancer screening and individual preferences. The underlying individual preferences were measured on the basis of the self-reported general willingness to spend money now in order to save money in the future and general preferences with regard to financial planning.Primary outcome measure Intention to participate in lung cancer screening.Results Individuals eligible for lung cancer screening who place less value on their future were around four times less likely to report an intention to participate in lung cancer screening than were those who valued their future (OR 3.86, 95% CI 1.89 to 7.90). A present-biassed individual (one with a tendency for immediate gratification) was also about four times less likely to report an intention to participate in screening than an individual with no present bias (OR 0.26, 95% CI 0.12 to 0.57).Conclusions Underlying individual preferences regarding the present and future significantly affect individuals’ intention to participate in lung cancer screening. Hence, provision of incentives may be necessary to encourage the targeted heavy smokers who may have a strong preferences for the present over future.